Thermo-mechanical fatigue of SiMo 4.06 turbocharger turbine housing: Damage operator approach. (November 2019) - Bartošák, Michal; Španiel, Miroslav; Doubrava, Karel
Abstract: This paper presents a lifetime calculation for the silicon-molybdenum cast iron turbine housing of a turbocharger under thermo-mechanical loading during a closed waste-gate cycle. The results of a transient heat-transfer finite element analysis are used as the main load parameter in the subsequent viscoplastic structural finite element analysis, where a stabilized stress-strain response is obtained by the time-efficient Direct Cyclic procedure implemented in Abaqus/Standard finite element software. The Damage Operator Approach is implemented in C++ code, and is used for continuous creep and fatigue damage calculations. The numerical results match the observed critical locations. Highlights: Damage operator is used for thermo-mechanical fatigue damage calculations Stabilized stress-strain response of the finite element model is obtained directly Viscoplastic material parameters are derived from uniaxial tests Thermo-mechanical fatigue damage is predicted for the turbine housing of a turbocharger Fatigue, creep and oxidation are taken into account in the damage calculation